2003
DOI: 10.1590/s0102-311x2003000700016
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum weight retention among women in Rio de Janeiro: a follow-up study

Abstract: This study presents follow-up results on trends in postpartum weight retention among women in the city of Rio de Janeiro, Brazil, at 0.5, 2, 6, and 9 months postpartum. The outcome variable, weight retention, was calculated by subtracting the reported pre-pregnancy weight from the observed weight at each interview. Statistical analyses used means and a 95% confidence interval for weight retention. Mean weight retention was 4.7, 4.1, 3.4, and 3.1kg at 0.5, 2, 6 and 9 months postpartum, respectively. At completi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0
18

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 12 publications
(22 reference statements)
3
35
0
18
Order By: Relevance
“…Most studies included primarily adult women. 23,[27][28][29][31][32][33]35,36,38,43,46 Four studies reported a mean age above 30 years, 23,27,28,36,46 one study below 20 years. 42 Two studies did not provide any information on their population's age 24,44 (Table 1).…”
Section: Qualitative Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies included primarily adult women. 23,[27][28][29][31][32][33]35,36,38,43,46 Four studies reported a mean age above 30 years, 23,27,28,36,46 one study below 20 years. 42 Two studies did not provide any information on their population's age 24,44 (Table 1).…”
Section: Qualitative Resultsmentioning
confidence: 99%
“…Tables 1-3 summarize the results of the qualitative analysis. Fifteen prospective studies, 23,24,[29][30][31][32][33][34][35][36]38,[40][41][42][43][44][45] five retrospective studies, 22,[25][26][27][28]37,46 and the control group from a randomized controlled trial 39 were included in the final analysis. Studies in which women were recruited around the time of delivery and then followed prospectively for postpartum body weight (ambivalent design, as baseline weight was assessed retrospectively) 24,29,30,[34][35][36][44][45][46] were considered as prospective in design, as we wanted to focus on the development of postpartum weight change.…”
Section: Qualitative Resultsmentioning
confidence: 99%
See 3 more Smart Citations